Utility of minimal preparation computed tomography colonography in detecting colorectal cancer in elderly and frail patients. Issue 12 (5th December 2018) - Meiklejohn, David J.; Ridley, Lloyd J.; Ngu, Meng C.; Cowlishaw, James L.; Duller, Alex; Ridley, William
Abstract: Background: Colorectal cancers result in substantial morbidity and mortality to the Australian society each year. The usual investigation for bowel malignancy is optical colonoscopy (OC), with computed tomography colonography (CTC) used as an alternative investigation. The catharsis and colon insufflation associated with these investigations pose a higher risk in the elderly and frail. Risks include perforation, serum electrolyte disturbance and anaesthesia/sedation risks. Minimal preparation computed tomography colonography (MPCTC) eliminates these risks. Aims: To audit the accuracy of a MPCTC programme for the investigation of colonic masses in symptomatic elderly and frail patients. Methods: This paper audits a 6‐year period of MPCTC in an Australian tertiary referral hospital. A total of 145 patients underwent MPCTC during the study period. Results: There were seven true positives, two false positives and two false negatives. Analysis of this population indicates a sensitivity of 0.78 (95% CI 0.51–1.05), specificity of 0.99 (95% CI 0.97–1.01), positive predictive value (PPV) of 0.78 (95% CI 0.51–1.05) and negative predictive value (NPV) of 0.99 (95% CI 0.97–1.01). These findings are concordant with other published studies. Conclusions: This audit confirms that minimal preparation CT colonography is a reasonable alternative to OC and CTC in detecting colorectal cancer in symptomatic elderly and frail patients, without the procedural risks inherent in more invasive investigations. For most patients, MPCTC ruled out significant colorectal carcinoma with a high NPV.